1993
DOI: 10.1080/09670879309371809
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sorghum diseases in Nigeria†

Abstract: A survey was conducted In farmers f~olds In N~ger~a durlng the 1990 cropplng season to determlne the prevalence of sorghum dlseases In the four major sorghum-grow~ng cl~mat~c zones (Sahel Sudan, northern Gulnea and southern Gu~nea) The follar dlseases anthracnose (Colletotrichum gram~nicola). oval leaf spot (Ramulispora sorgh~cola), sooty strlpe (Ramul~ spora sorghi) and grey leaf spot (Cercospora sorghi) were w~dely dlstrlbuted Anthracnose was predominant throughout the areas s u ~e y e d wlth -40% leaf area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The disease is easily recognized by the characteristic symptoms of circular to elliptical red spots with few to numerous acervuli on leaf laminas (Tarr 1962;Marley et al 2004). Sorghum anthracnose occurs in all sorghum growing regions of the world (Pande et al 1993;Ngugi et al 2002), causing yield losses as high as 50% (Harris et al 1964;Powell et al 1977).…”
Section: Introductionmentioning
confidence: 97%
“…The disease is easily recognized by the characteristic symptoms of circular to elliptical red spots with few to numerous acervuli on leaf laminas (Tarr 1962;Marley et al 2004). Sorghum anthracnose occurs in all sorghum growing regions of the world (Pande et al 1993;Ngugi et al 2002), causing yield losses as high as 50% (Harris et al 1964;Powell et al 1977).…”
Section: Introductionmentioning
confidence: 97%
“…A recent report by Pande et al (1997) supports this findings. The disease appears to have also increased in the SGS as results obtained in this survey indicated higher incidence than other reports (e.g., Adeoti, 1993;Pande et al, 1993). Reports by Tyagi (1980) and Selvaraj (1980) had indicated that traditional cultivars were more susceptible than improved cultivars.…”
Section: Discussionmentioning
confidence: 51%
“…Disease severity based on a 1-9 rating scale, where 1 = clean panicle with no infection, 2 = <1% seeds infected/head, 3 = 1-5% seeds infected/head, 4 = 6-10% seeds infected/head, 5 = 11-20% seeds infected/head, 6 = 21-35% seeds infected/head, 7 = 36-50% seeds infected/head, 8 = 51-75% seeds infected/head and 9 = >75% seeds infected/ head. The first elaborate attempt at showing the distribution of smuts in Nigeria was reported by Selvaraj (1980) based on surveys conducted from 1975 to 1978 while Pande et al (1993) further reviewed the status of these diseases on sorghum in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is widespread in the sorghum growing areas in Nigeria (Pande et al 1993). It is Correspondence: B. S. Bdliya, Department of Crop Protection, University of Maiduguri, P. M. B.…”
Section: Introductionmentioning
confidence: 99%